Physiological changes of post-puerulii spiny lobster (Panulirus ornatus Fabricius, 1798) fed low protein to energy ratio diets supplemented with black soldier fly (Hermetia illucens) meal - Saputra, Ishaaq (Curtin University, 2024)
The ornate spiny lobster (Panulirus ornatus) is a commercially valuable marine rock lobster with potential for aquaculture. Nutrition in spiny lobster diets is a key focus, with a particular interest in the protein-to-energy ratio and the impact of reducing fishmeal with alternative ingredients such as black soldier fly meal. Fish protein hydrolysate supplementation in low P/E ratio diets with black soldier fly meal inclusion shows promise for enhancing the physiological and immunological responses of juvenile lobsters, though further validation at a larger scale is recommended.